(−)-Epicatechin Reduces Neuroinflammation, Protects Mitochondria Function, and Prevents Cognitive Impairment in Sepsis-Associated Encephalopathy. (24th May 2022) - Ling, Jianmin; Wu, Yanqing; Zou, Xiaojing; Chang, Yanmin; Li, Gang; Fang, Minghao
Abstract : Sepsis-associated encephalopathy is a common neurological complication of sepsis. Despite advances in pathological and diagnostic investigations, its treatment remains a major challenge. In sepsis-associated encephalopathy, neuroinflammatory overactivation and mitochondrial damage are thought to contribute to cognitive and behavioral impairments. In this study, we found that administration of (−)-Epicatechin, a dietary flavonoid of the flavan-3-ol subgroup, improves memory deficits and behavior performance by ameliorating neuroinflammation, regulating mitochondria function, enhancing synaptic plasticity, and reducing neuronal loss in a mouse model of lipopolysaccharide-induced sepsis. We further show that the AMPK signaling pathway might be among the mechanisms involved in the beneficial memory effects. Our data demonstrated the potential of (−)-Epicatechin as a new drug candidate for the treatment of sepsis-associated cognitive impairment by targeting AMPK.